Sedation vs intubation for patients with acute stroke undergoing thrombectomy: reply - Bösel, Julian; Schönenberger, Silvia (The journal of the American Medical Association, 2017)
In Reply Drs See and Ducruet raise a number of concerns about our trial. The study was designed to investigate short-term clinical outcomes, whereas longer-term outcomes, which are also important, should be addressed in a multicenter trial. The MR CLEAN data that See and Ducruet cite to question our...